2014
DOI: 10.1038/ejhg.2014.57
|View full text |Cite
|
Sign up to set email alerts
|

Clinical spectrum and outcomes in families with coronal synostosis and TCF12 mutations

Abstract: TCF12 mutations have been reported very recently in coronal synostosis. We report several cases of familial coronal synostosis among four families harbouring novel TCF12 mutations. We observed a broad interfamilial phenotypic spectrum with features overlapping with the Saethre-Chotzen syndrome. TCF12 molecular testing should be considered in patients with unilateral-or bilateral-coronal synostosis associated or not with syndactyly, after having excluded mutations in the TWIST1 gene and the p.Pro250Arg mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 7 publications
5
31
3
Order By: Relevance
“…The single largest contributor to these diagnoses is TCF12 , which encodes a partner protein of TWIST1 particularly critical for coronal suture development [27]. Two follow-up studies have confirmed the importance of TCF12 mutations in coronal craniosynostosis, both in the context of familial mutations [37], and in a more general screen of craniosynostosis [29]. Given the haploinsufficiency mechanism of TCF12 mutations, heterozygous deletions are also expected to be pathogenic and this has been confirmed in two reports [38, 39].…”
Section: Non-syndromic Craniosynostosismentioning
confidence: 99%
“…The single largest contributor to these diagnoses is TCF12 , which encodes a partner protein of TWIST1 particularly critical for coronal suture development [27]. Two follow-up studies have confirmed the importance of TCF12 mutations in coronal craniosynostosis, both in the context of familial mutations [37], and in a more general screen of craniosynostosis [29]. Given the haploinsufficiency mechanism of TCF12 mutations, heterozygous deletions are also expected to be pathogenic and this has been confirmed in two reports [38, 39].…”
Section: Non-syndromic Craniosynostosismentioning
confidence: 99%
“…Although 81% of the individuals with TCF12 mutations presented with apparent cNCS, some of the affected individuals had developmental delays and dysmorphic features overlapping with the Saethre-Chotzen syndrome [Sharma et al, 2013]. More recently, the phenotypic spectrum of TCF12 mutations has been extended to include possible facial and limb anomalies, and intellectual disability [Di Rocco et al, 2014; Le Tanno et al, 2014; Paumard-Hernandez et al, 2015; Piard et al, 2015]. Based on these observations, it is reasonable to recommend TCF12 testing for all patients with cCS, with or without associated anomalies.…”
Section: Genetic Etiopathogenesis Of Craniosynostosismentioning
confidence: 99%
“…Facial growth appears not greatly affected ( Fig. 10 ) [Di Rocco et al, 2014;Goos et al, 2016]. The phenotype is variable, including non-penetrance of the TCF12 gene, which encodes a basic helix-loop-helix transcription factor [Sharma et al, 2013].…”
Section: Tcf12-related Craniosynostosismentioning
confidence: 99%